PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PEMBIAYAAN BERMASALAH PADA BANK UMUM SYARIAH (BUS) DAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) - Sherly Yolanda; Ariusni Ariusni (Universitas Negeri Padang, 2019)
This study was conducted to examine the factors affecting Non Performing Financing (NPF) in Sharia Commercial Bank and Sharia Rural Bank in Indonesia such as: Capital Adequacy Ratio (CAR), Return On Assets (ROA), Inflation, and Exchange Rate. The data used are secondary data in the form of time series of monthly data from 2015 to 2018.The method used are: (1) Ordinanry Least Square (OLS), (2) Classical Assumption Test which is processed through Eviews 8.0 application. The results of the study show that (1) Capital Adequacy Ratio (CAR) has a negative and significant effect on Non Performing Finansial (NPF) on Sharia Commercial Bank and Sharia Rural Bank (2) Return On Assets (ROA) has a negative and not significant effect on Non Performing Finansial (NPF) on Sharia Commercial Bank and on Sharia Rural Bank has a positive and significant effect. (3) inflation has a negatif and not significant effect on Sharia Commercial Bank and Sharia Rural Bank. (4) Exchange Rate has a negatif and not significant effect on Non Performing Finansial (NPF) on Sharia Commercial Bank and on Sharia Rural Bank has a positive and not significant effect